Injuries associated with bunk beds occurring at schools: results using a US national data base. Issue 5 (31st May 2018) - Loder, Randall T; Momper, Luke
Abstract : Objective: To investigate bunk bed injuries occurring across all educational institutions using a national data base. Methods: National Electronic Injury Surveillance System data for the years 2006–2015 associated with bunk beds was analysed. Results: There were an estimated 639 700 emergency department (ED) visits for bunk bed injuries; 1.3% occurred at school. Those occurring at school were older than those not at school (18.2 vs 12.8 years), and more commonly female (56.4% vs 40.6%), Caucasian (91.7% vs 68.3%) and associated with alcohol (10.8% vs 0.4%). For those occurring at school, the average age for those involving the trunk, upper extremity, lower extremity and head/neck areas was 17.9, 14.9, 19.2 and 18.7 years, respectively (p<10 −4 ). A fracture was present in 6.4%, 52.3%, 21.2% and 9.6% of the trunk, upper extremity, lower extremity and head/neck areas, respectively (p=0.009). Males had a higher percentage of lacerations and females had a higher percentage of internal organ injuries. The vast majority of the fractures and strain/sprains occurred in the extremities; lacerations in the head/neck and contusion/abrasions predominantly involved the extremities and head/neck. Conclusions: 1.3% of all ED visits due to bunk bed injuries occurred in places of education. The majority of these were during college age. Prevention strategies should be directed at educational institutions and students, as well as following proper bunk bed equipment guidelines. Education regarding alcohol risks might assist college age students.